Eksistensi Guru PAK dalam Penguatan Karakter Musyawarah Mufakat Kepada Siswa di Sekolah - Endi Tanaem; Yakobus Adi Saingo (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
Indonesia as a democratic country rich in diversity, requires a deliberative approach in social interactions to reach agreements and overcome differences. Consensus deliberation not only functions as a method of decision making, but also as a means of developing students' social skills, such as communication and empathy. This article aims to analyze the existence of PAK teachers in strengthening the value of deliberation and consensus among students in schools. The method used is qualitative, where data/information collection is obtained from interviews, observation and literature study. Data analyzed in a reduced manner revealed the results of the study that there are three main roles of PAK teachers through the learning process in schools, including: instilling the importance of deliberation which can be applied through direct teaching, contextualization, and as a discussion facilitator. The application of the value of deliberation and consensus by PAK teachers contributes to academic understanding and the formation of student character. There is a need to develop skills by PAK teachers in facilitating discussions and creating inclusive activities, so that students can experience the real benefits of consensus deliberation in everyday life. With the spirit of upholding mutual deliberation in various school activities, PAK teachers have trained students to be open through conducive communication and willing to accept various forms of differences of opinion so that every decision made is the result of mutual agreement.